Indonesia’s Contra-Productive Regulation against the Rights of Unskilled Workers for Balinese in New Zealand - Desak Putu Dewi Kasih; Ida Bagus Wyasa Putra; Lukas Banu; Ida Bagus Erwin Ranawijaya; Ida Bagus Aswin Pranawa Sidhi (Sriwijaya Law Review, 2023)
New Zealand relies heavily on its agricultural industry. There are over 4,150 cultivators in the horticultural sector. They require the cooperation of foreign workers. Some of them were recruited from Indonesia, where most of the labour force is poor and unskilled. This research is conducted to analyse the compatibility of legislation and policy in Indonesia and New Zealand. So, they may enjoy their rights and possibilities for choosing, acquiring, or migrating from one work to another and earning a fair salary, whether domestically or internationally. Based on the contextual law method, it has been concluded that New Zealand’s laws provide excellent regulations for such enjoyment. Regarding the equal enjoyment of their fundamental employment rights, Indonesian Law and policy have failed to meet the needs of employees. This article demonstrates the Indonesian and New Zealand legal systems’ capacity and the need for Indonesian Law to be reconstructed to fulfil workers' demands.